Does digital finance affect the quality of economic growth? Analysis based on Chinese city data - Liu, Tinghua; Hu, Mengyuan; Elahi, Ehsan; Liu, Xiao (Frontiers in Environmental Science, 2022)
With the support of national policies and continuous emergence and innovation of emerging technologies, digital finance has developed rapidly in China. Can digital finance become a new driving force to promote quality development of economic growth? This study empirically examined the effect mechanisms of digital finance on the quality of economic growth. The study used the entropy weight and technique for order preference by similarity to an ideal solution method to construct a comprehensive index system of economic growth quality. From 2011 to 2019, the panel data of 272 cities in China were collected. The study found that digital finance can promote the quality of China’s economic growth in the long run; when digital finance development increases by one unit, the quality of economic growth will increase by 0.013%, and the effect is more significant in less developed regions. The digital finance coverage, depth of use, and degree of digitalization had a significant impact on the quality of economic growth. The mechanisms showed that digital finance can promote the quality of economic growth by promoting and upgrading the industrial structure. In addition, we used the threshold model to test the non-linear relationship between digital finance and the quality of economic growth. Furthermore, the results showed that when digital finance was at a low level, it had a negative effect on the quality of economic growth. As digital finance developed further, it had a significant effect on the quality of economic growth, and this effect gradually slowed down. Moreover, we found that digital finance played a more significant role in promoting the quality of economic growth in central and western regions and areas where traditional finance was underdeveloped. Based on this study, developing countries should strengthen the construction of digital infrastructure and give full play to the role of digital finance in improving the quality of economic growth, so as to promote sustainable and healthy economic development.